Patterns of Urachal Remnant Involvement by Urothelial Carcinoma: Intraluminal Noninvasive Spread Can Mimic a Deep-seated Bladder Invasion. (April 2019) - Han, Lisa; Gallan, Alexander; Paner, Gladell P.
Abstract : Benign urachal remnants can be encountered in the adult urinary bladder and it is recognized that these can uncommonly give rise to urachal urothelial carcinoma. However, urachal remnants containing urothelial carcinoma incidentally encountered in cystectomies for bladder cancer has not been previously described. Herein, we present 8 adult bladder cancer cystectomies with incidental urachal remnants containing urothelial carcinoma. All 8 incidental urachal remnants with tumor were located at the dome that varied from small tubular to tubulocystic structures and contained urothelial carcinoma in situ (CIS) (6), noninvasive high-grade papillary urothelial carcinoma (PUC) (1), and coexistent noninvasive high-grade PUC and urothelial CIS (1). Six of the 8 urachal remnants with tumor also showed benign urothelial cells (2), mixed urothelial and glandular cells (2), and cuboidal cells (2). The bladder mucosa directly above the remnant showed urothelial CIS (4), PUC (1), concomitant PUC and urothelial CIS (1), invasive urothelial carcinoma (1), and benign urothelium (1); only 1 remnant intermingled with invasive urothelial carcinoma nests. Two remnants with tumor were at a region away from the main bladder tumor including the one overlaid by benign urothelium. The remnant with tumor extended into the upper half (5) or lower half (3) of muscularis propria (MP) and if misinterpreted as MP invasion, 5 of 8 bladder tumors will be overstaged. In conclusion, urachal remnant can have an early involvement by urothelial CIS or PUC similar in the bladder proper lumen. Urothelial carcinoma involving the urachus can be divided into a: (a) contiguous spread from a bladder urothelial carcinoma, (b) separate (noncontiguous) focus concomitant to bladder urothelial carcinoma, and (c) primary urachal urothelial carcinoma. Caution is warranted not to over interpret urachal remnant involvement by noninvasive urothelial carcinoma as an invasive tumor focus which could lead to overstaging.